Raw Secondary Metabolites Application of Two Trichoderma harzianum Isolates towards Vascular Streak Dieback on Cocoa Seedlings - Loekas Soesanto; Endang Mugiastuti; Abdul Manan (Indonesian Coffee and Cocoa Research Institute, 2019)
Vascular streak dieback is an important disease on cocoa that recently is still difficult to control. This research aimed to study the raw secondary metabo- lites application effectiveness of Trichoderma harzianum T10 and T213, or their combination to vascular streak dieback and its effect on growth and on phenolic compound of cocoa seedlings. Randomized block design was used with nine replicates. The treatments were control, secondary metabolites of T. harzianumT10 and T213, their combination and fungicide with active ingredient of phosphic acid. Variables observed were incubation period, disease intensity, plant height, number of leaves, wieght of fresh and dry plants, weight of fresh and dry roots, roots length, and phenolic compound. Result of the research showed that the raw secondary metabolites of T. harzianum T10 could suppress the disease inten- sity and delay the incubation period as 62.17 and 24.97%, respectively. The raw secondary metabolites of T. harzianum T213 and T10 combination could increase plant height 36.21%, number of leaves 19.07%, fresh weight of plant 20.6%, dry weight of plant 17.5%, fresh weight roots 27%, dry weight of root 34.36%, and roots length 21.30%. All raw secondary metabolites of T. harzianum were able to increase phenolic compounds (saponins, tannins, and glycosides) qualitatively of cocoa seedlings.